Government Forecasts of Budget Balances Under Asymmetric Loss: International Evidence - Jan-Christoph Rülke; Christian Pierdzioch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study the loss function of 15 European governments as implied by their budget balance forecasts. Results suggest that the shape of the loss function varies across countries. The loss function becomes more asymmetric as the forecast horizon increases and in advance of parliamentary election. Compared to that, government ideology does not affect the shape of the loss function. Under a fiscal rule, government agencies experience a higher loss when overpredicting the fiscal balance compared to an underprediction of the same size. We also document that under an asymmetric loss function government forecasts look more rational compared to a symmetric loss function. This may explain why government agencies' forecasts have been found to be too optimistic (Frankel 2012).
Keywords: E62; H50; E27; 330